Passive air sampling of polycyclic aromatic hydrocarbons, organochlorine pesticides and polychlorinated biphenyls a pilot study of POPs in the Philippine atmosphere - Cayetano, Mylene B. Gonzaga; Quirit,Leni L. (Quezon City Institute of Environmental Science and Meteorology, College of Science, University of the Philippines Diliman, 2007)
The feasibility of using passive air sampler (PAS) in the determination of the concentration of persistent organic pollutants (POPs) in inhalable ambient air as apioneering study in the Philippines was investigated.
Thesis (M.S. Environmental Science)--University of the Philippines Diliman
Keywords: Air -- Pollution -- Measurement; Air sampling apparatus